The Role of Education in Achieving the Right for Decent Human Life - A. G. Kislov; Y. M. Kropaneva (Образование и наука)
The paper looks at the issue of the human right for decent life and its direct link with education that facilitates the observance of civil, political, economic and cultural rights and is regarded both as a condition and consequence of fulfilling the decent life idea. The chances of a non-educated and poorly educated people for the decent life are doubtful, not to speak of the civil and political rights that can’t be properly exploited. The authors give the retrospective analysis concerning the formation process of the human right for decent life; its theoretical and practical variations including the domestic ones being described along with the problem of its ethical content reflected in normative legal acts and indices of economic development. Education leads to demy- thologizing and rejecting the ideological aspect of the above human right idea, the latter being the necessary complex universal multifunctional instrument for social self- development, rather then a judicial phenomenon. The authors made an attempt to reconcile the pathos of the human right adherents and the skeptics reducing the idea to the declarative unverifiable myth or ideology. The research output can be used both for goal-setting in educational sphere and normative legal acts development concerning education and human rights.